FACTORS AFFECTING FARMERS' DECISIONS TO APPLY HYDROPONIC SYSTEMS IN TARAKAN CITY - Nurlela Machmuddin (Agricultural Socio-Economics Journal, 2023)
Tarakan City has limited agricultural land potential and is less productive so that most of the consumption needs for vegetables are imported from outside the island of Tarakan. It is hoped that with the development of hydroponic technology, the community can meet the needs of vegetables independently. The purpose of this study was to determine the factors that influence the decision of farmers to implement a hydroponic system. The research is located in Tarakan City with the research period from April to October 2021. The method of determining respondents was carried out intentionally to 40 respondents with the consideration that the community had obtained information about hydroponic system, either through direct agricultural extension workers, from friends or through other electronic media. such as television, YouTube, Facebook and other social media. To find out the factors that affect farmers' opportunities to apply hydroponic system, an analysis is carried out using the logit function approach. Analysis of the factors that influence farmers' decisions to apply hydroponic system using logit regression function analysis obtained a Nagelkerke R2 value of 0.494 meaning that the variation of the independent variables included in the model was able to explain 49.4% of the existing phenomena and the remaining 50.6% was explained by other variables. The variable hydroponic planting experience (X4) has a significant and significant effect at the 5 %, meaning that the more often people cultivate hydroponic plants, the greater the opportunity to apply hydroponic system, while age (X1), formal education (X2), Membership Dummy in the farmer group (X3), and Dummy nutrient costs (X5) are not significant. One of the obstacles for farmers in applying hydroponic system is the cost of purchasing nutrients.